Diversity and distribution pattern of bioactive compound potential seaweed in Menganti Beach, Central Java, Indonesia - DWI SUNU WIDYARTINI; HEXA APRILIANA HIDAYAH; ACHMAD ILALQISNY INSAN (Society for Indonesian Biodiversity, 2023)
Abstract. Widyartini DS, Hidayah HA, Insan AI. 2023. Diversity and distribution pattern of bioactive compound potential seaweed in Menganti Beach, Central Java, Indonesia. Biodiversitas 24: 1125-1135. Seaweed has great potential in the pharmaceutical industry. This study aims to obtain data on the diversity and distribution of bioactive compound potential seaweeds collected from Menganti Beach. The research applied the survey and random transect sampling in each substrate type. The variables were species diversity, distribution pattern, and bioactive compound potential. The main parameters were the number of species and the number of individuals of each species of seaweed. The supporting parameters were depth, salinity, temperature, and pH. The data were analyzed by calculating the Shannon-Wiener diversity, Simpson dominance, and Morisita indices using Primer 7 software. The results showed that 21 species have bioactive compound potential. There were seven species (33 %) of Chlorophyta, including Caulerpa leltilifera, C. racemosa, C. taxifolia, Ulva lactuca, U. intestinalis, Valonopsis pacynema, and Codium tomentosum. Twelve species (57%) of Rhodophyta, including Callophyllis crispata, Chondrus crispus, Eucheuma spinosum, Halymenia harveyana, Gigartina stellata, Gracilaria gigas, G. canaliculata, G. lichenoides, G. verrucosa, Palmaria palmata, Portieria hornemannii, and Rhodymenia palmata; and two species (10%) of Phaeophyta, including Padina australis and Sargassum crassifolium. The diversity of seaweed was moderate (0.903-1.153). The dominance index (0.559-0.68) indicates no dominance, and the seaweed distribution pattern is grouping.